“A STUDY ON EMPLOYEE ABSENTEEISM AND EMPLOYEE MORALE WITH REFERENCE TO INTERNATIONAL BAKERY’S IN PUDUCHERRY” - Robinson, N.; M, UmaRaman. (International Journal of Psychosocial Rehabilitation, 2020)
The non-appearance is the central point that influences the association development. Non- attendance is the one of the most widely recognized working environment confronting businesses in today work place. The investigation on representative non-appearance and worker moral in over the top unlucky deficiencies can equalatedcreassed efficiency and significant impact on organization account. An organized survey is readied and the information are gathered from the IBP. The information is gathered are dissected utilizing the measurable apparatuses like rate strategy, chi-square, Correlation, mean standard deviation.